2023
DOI: 10.3390/gels9030187
|View full text |Cite
|
Sign up to set email alerts
|

Development of Tofacitinib Loaded pH-Responsive Chitosan/Mucin Based Hydrogel Microparticles: In-Vitro Characterization and Toxicological Screening

Abstract: Tofacitinib is an antirheumatic drug characterized by a short half-life and poor permeability, which necessitates the development of sustained release formulation with enhanced permeability potential. To achieve this goal, the free radical polymerization technique was employed to develop mucin/chitosan copolymer methacrylic acid (MU-CHI-Co-Poly (MAA))-based hydrogel microparticles. The developed hydrogel microparticles were characterized for EDX, FTIR, DSC, TGA, X-ray diffraction, SEM, drug loading; equilibriu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Changes in the spherical shape can also be caused by the adhesive nature of chitosan and the type of substrate on which the drying process was carried out [ 29 , 30 ]. However, the presence of porous surfaces in coated microparticles had a significant effect on water retention and uptake of physiological media, which consequently improved swelling and affected drug release [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Changes in the spherical shape can also be caused by the adhesive nature of chitosan and the type of substrate on which the drying process was carried out [ 29 , 30 ]. However, the presence of porous surfaces in coated microparticles had a significant effect on water retention and uptake of physiological media, which consequently improved swelling and affected drug release [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is available as high, medium, and low molecular-weight chitosan. This polymer is cationic, contains nitrogen in its chemical structure, and has ability to form polyelectrolyte complexes [62]. It becomes water soluble by forming carboxylate salts like acetate, citrate, formate, malate, glycolate, pyruvate, lactate, and ascorbate.…”
Section: Chitosanmentioning
confidence: 99%
“…[8,14] Previous research delivering JAK inhibitors from hydrogels only showed release over a few days. [15][16][17][18] A notable example showed metalloprotease-triggered delivery of tofacitinib for atopic dermatitis in vitro from a polyethylene glycol hydrogel, but with release of ≈40% at 48 h. [19] Despite these illustrations of controlled release, extending release for additional days and even weeks is desired, particularly to avoid the need for repeated administrations where compliance is a major barrier to use and clinical translation.…”
Section: Introductionmentioning
confidence: 99%